2010
DOI: 10.5483/bmbrep.2010.43.10.704
|View full text |Cite
|
Sign up to set email alerts
|

Swedish mutation within amyloid precursor protein modulates global gene expression towards the pathogenesis of Alzheimer's disease

Abstract: The Swedish mutation (K595N/M596L) of amyloid precursor protein (APP-swe) has been known to increase abnormal cleavage of cellular APP by Beta-secretase (BACE), which causes tau protein hyperphosphorylation and early-onset Alzheimer's disease (AD). Here, we analyzed the effect of APP-swe in global gene expression using deep transcriptome sequencing technique. We found 283 genes were down-regulated and 348 genes were up-regulated in APP-swe expressing H4-swe cells compared to H4 wild-type cells from a total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 24 publications
1
33
1
Order By: Relevance
“…In a proteomic-wide study using human Jurkat T lymphocytes, cytoskeletal proteins including vimentin were found as prime targets of Omi/HtrA2 protease [36]. Several studies have also suggested that vimentin in response to certain apoptosis stimuli is cleaved by multiple caspases, resulting in diverse vimentin fragments [43].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In a proteomic-wide study using human Jurkat T lymphocytes, cytoskeletal proteins including vimentin were found as prime targets of Omi/HtrA2 protease [36]. Several studies have also suggested that vimentin in response to certain apoptosis stimuli is cleaved by multiple caspases, resulting in diverse vimentin fragments [43].…”
Section: Discussionmentioning
confidence: 97%
“…4e, lane 1). These are most likely due to stress-related conditions caused by overexpression of APP mutation that eventually lead to increased degradation of vimentin or affect gene expression and genes related to signal pathways involved in degradation of cytoskeleton proteins [36] (Fig. 4e, lane 1).…”
Section: Increased Interaction Between Omi/htra2 and Vimentin In Humamentioning
confidence: 98%
See 1 more Smart Citation
“…Cells expressing Swedish mutant APP have dramatic increases (up to 6- to 8-fold) in Aβ 1 – 40 and Aβ 1 – 42 production via elevated endoproteolytic cleavage at the β-secretase site [4], [5]. Our previous study also found global alterations in gene expression, including genes associated with AD pathogenesis in APP -Swedish mutant cells [6]. Insulin-like growth factor binding protein-3 ( IGFBP3 ) was one gene whose expression was significantly down-regulated in APP-Swedish mutant cells.…”
Section: Introductionmentioning
confidence: 61%
“…H4 and H4-sw cells were cultured as previously described in Dulbecco's modified Eagle media (DMEM; Gibco/BRL) containing 10% fetal bovine serum (FBS; Gibco/BRL), 100 U/mL penicillin (Gibco/BRL), 100 µg/mL streptomycin (Gibco/BRL), and 2 mM L-glutamine (Gibco/BRL) [6]. To maintain H4-sw cells, 500 µg/mL geneticin (Gibco/BRL) was added to the growth media.…”
Section: Methodsmentioning
confidence: 99%